IMPLEMENTASI KEBIJAKAN NET ZERO EMISSIONS (NZE) DI KOTA SEMARANG - Tjhang Mirza Prima Bredy Putra; rina Martini (Journal of Politic and Government Studies, 2026)
This study aims to analyze the implementation of the Net Zero Emissions policy in Semarang City and identify the actors involved in the policy implementation process. This study uses qualitative research methods with a descriptive approach. Data collection techniques include interviews, documentation, and literature reviews of relevant policy documents and reports.. The Semarang City Government has also conducted an emissions inventory and reporting as part of its integrated emissions control efforts with the national system. Its implementation involves several key actors: the Regional Development Planning Agency (Bappeda); the Environmental Agency (DLH); the Transportation Agency (Dishub); and the community as a stakeholder in implementing low-carbon behaviors in daily life.